A cosmetovigilance survey in Malaysia - Zamli, Mazlina Amira; Ai, Nur'ain; Awadh, Ammar Ihsan JawaD; Ab. Hadi, Hazrina (2015)
Despite the high popularity of cosmetics among consumers, there is still lack of studies on cosmetovigilance in Malaysia. The cosmetic safety issues may be associated with the consumers’ level of knowledge, practice, attitude, and perception. The aim of this study was to assess cosmetovigilance-related knowledge, practices, attitudes, and perceptions of consumers in Malaysia. To this aim, a SurveyMonkey questionnaire comprised of five sections: demographic profile, knowledge on cosmetic safety, practice towards cosmetics, attitude towards cosmetic safety, and perception towards cosmetics, was distributed to 552 consumers in Malaysia by snowball sampling method from April to June 2015. Then, the data was analyzed using Statistical Package for Social Sciences (SPSS) version 20. The reliability coefficient for knowledge, attitude, and perception parts were 0.75, 0.71 and 0.66 respectively. The results of this study revealed more than half of them had poor knowledge (57.2%), attitudes (60.3%), and perceptions (59.2%) on cosmetics and its safety. Regardless, their practice towards cosmetics was acceptable. Total knowledge score showed significant difference with gender (P<0.001) and monthly expenditure (P=0.001) while total attitude score showed statistical significance difference with respect to gender (P=0.008), age (P <0.001), marital status (P<0.001), education (P=0.014), occupation (P<0.001), income range (P=0.009) and monthly expenditure (P=0.013). In conclusions, the level of cosmetovigilance-related knowledge, practices, attitudes, and perceptions of consumers in Malaysia are still insufficient. The findings are hoped to give some insights to the authorities to elevate the knowledge and attitude of consumers on cosmetovigilance issues and improve their practice and perception toward cosmetics.